Modeling the Stability of the Housing and Construction Complex Based on Organizational and Economic Interaction of Entities - N. N. Shelomentseva; O. V. Grushina (Управленческие науки)
The article addresses the structure of the socio-economic system of the housing and construction complex (HCC), focusing on the organizational and economic interaction of its participants against the backdrop of entropy-driven macroeconomic influences. The study aims to identify management methods, from a system-information approach, that allow the system to reach a new level of sustainable disequilibrium with the environment while maintaining homeostasis. Since the primary factor in the housing construction sector is the availability of built housing, the first research task was a detailed examination of household housing provision in Russia as a whole and in the Irkutsk region, based on census data from 2002, 2010, and 2020. As a result, the idea of the “best” structure of the housing stock in terms of the number of rooms corresponding to the composition of households was proposed. Achieving the “optimal” housing provision for the population requires timely organizational and economic changes, one of which is the introduction of project financing. To reach a new level of sustainable equilibrium in the HCC system, coordinated actions among all stakeholders are necessary to minimize the gap between the actual and the “optimal” housing stock structure. The second research objective was to find a solution to the multi-criteria problem of aligning the interests of economic entities in housing construction. A genetic algorithm in MATLAB was used for this purpose. Acceptable options for all participants were selected from a set of Pareto-optimal alternatives based on the preferences of the decision-maker. The state was imperatively assigned this role, with the optimization criterion being the minimization of the gap between the “optimal” and actual housing provision for households of various sizes. The modeling results indicated that effective collaboration towards a common goal is possible; however, the cost factor is inevitably passed on to consumers. The study’s findings will be of interest to students and graduate students studying construction economics, as well as to banking professionals, regional authorities, and specialists in the field of housing construction.